Synthesis of Homo‐Metallic Heavier Analogues of Cyclobutene and the Cyclobutadiene Dianion. Issue 20 (27th February 2023) - Zheng, Xiongfei; Crumpton, Agamemnon E.; Protchenko, Andrey V.; Ellwanger, Mathias A.; Heilmann, Andreas; Aldridge, Simon
Abstract: The reduction of the boryl‐substituted Sn II bromide {(HCDippN)2 B}Sn(IPrMe)Br with 1.5 equivalents of potassium graphite leads to the generation of the cyclic tetratin tetraboryl system K2 [Sn4 {B(NDippCH)2 }4 ], a homo‐metallic heavier analogue of the cyclobutadiene dianion. This system is non‐aromatic as determined by Nucleus Independent Chemical Shift Calculations (NICS(0)=−0.28, NICS(1)=−3.17), with the primary contributing resonance structures shown by Natural Resonance Theory (NRT) to involve a Sn=Sn double bond and 1, 2‐localized negative charges. Abstraction of the K + cations or oxidation leads to contraction or cleavage of the Sn4 unit, respectively, while protonation generates the neutral dihydride 1, 2‐Sn4 {B(NDippCH)2 }4 H2 (a heavier homologue of cyclobutene) in a manner consistent with the predicted charge distribution in the [Sn4 {B(NDippCH)2 }4 ] 2− dianion. Abstract : The reduction of {(HCDippN)2 B}Sn(IPrMe)Br with 1.5 equivalents of KC8 generates the cyclic tetra‐tin tetra‐boryl system K2 [Sn4 {B(NDippCH)2 }4 ], a homo‐metallic heavier analogue of the cyclobutadiene dianion. This system is non‐aromatic as determined by Nucleus Independent Chemical Shift Calculations, with the principal resonance structures shown to involve a Sn=Sn double bond and 1, 2‐localized negative charges.